Global publication trends on zakat management strategy: A bibliometric analysis - Azwar, Azwar; Nasir, Mohd Norzi bin (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study analyzed global publication trends on zakat management strategies using a bibliometric approach.Methodology – A quantitative method was employed through bibliometric analysis of the Scopus database, covering publications from 2000 to 2024.Findings – The results show a fluctuating but overall increasing trend in zakat management research. No researcher dominates the field, with most authors contributing only to 1-3 publications. Saad and Widiastuti are the most productive authors (three publications each), whereas S. Javaid is the most cited (57 citations). The Journal of Islamic Marketing is the leading publication medium, with five articles. Topic mapping indicates that zakat, Indonesia, Malaysia, strategy, and model are the most frequently discussed themes, highlighting the research focus on zakat management in Indonesia and Malaysia. Emerging topics include financial technology, Covid-19, and crisis adaptation, whereas governance, zakat distribution, and institutional quality remain underexplored, presenting opportunities for further research.Implications – These findings provide valuable insights for policymakers and zakat practitioners in developing efficient management models that integrate financial technology and crisis resilience. Educational institutions can also utilize these insights to design relevant curricula and training programmes. Additionally, this study identifies future research opportunities for the effectiveness of financial technology in zakat management and cross-country comparative analyses.Originality – This study offers a comprehensive bibliometric analysis of zakat management strategies and identifies key trends, influential authors, and leading publication sources. This study contributes new insights into emerging research areas and gaps, advancing the understanding of zakat management practices globally.